Memory and rejuvenation in a quasicrystal. (21st December 2020) - Joshi, D. C.; Gebresenbut, G.; Pay Gomez, C.; Mathieu, R.
Abstract: The glassy features of a single crystal of the icosahedral quasicrystal i -GdCd7.5 were investigated by means of squid magnetometry. The temperature-dependent zero-field–cooled magnetization was recorded on re-heating from low temperatures after halts in the cooling. The results evidence dynamical features akin to those of archetypal spin glasses, such as aging, memory, and rejuvenation. The results are compared to those of model spin glasses with different spin dimensionality, suggesting a qualitative similarity to the behaviour of metallic RKKY "Heisenberg" spin glasses.